Low‐alkali borosilicate glass microspheres from waste cullet prepared by flame synthesis. (17th June 2021) - Larionau, Pavel; Hujova, Miroslava; Michalková, Monika; Mahmoud, Mokhtar; Švančárková, Anna; Galusková, Dagmar; Parchoviansky, Milan; Bernardo, Enrico; Galusek, Dušan; Kraxner, Jozef
Abstract: Although glass recycling is considered to be a default method for glass waste management, fine fractions of container soda‐lime glass, or cullet of other compositions are still landfilled. This happens despite existing alternatives. Success could lie in advanced upcycled products that bring higher economic motivation for the implementation in industry, but these are often connected to alternative ways of product synthesis. We provide an example of waste glass upcycling by the preparation of glass microspheres (GM) from specialty low‐sodium alumino borosilicate‐based glasses via flame synthesis (FS). GM and the precursors, either from colorless medical vials or glass fibers, were characterized by scanning electron microscopy (SEM), simultaneous thermal analysis coupled with differential thermal analysis (STA‐DTA), and image analysis. A dynamic corrosion test was performed and evaluated via ion‐coupled plasma with optical emission spectroscopy (ICP‐OES) to observe corrosion kinetics products. FS has proved to be a fast method of waste glass processing into GM. This article, besides the characterization of the starting material and final products, also suggests the possibility of processing for other landfilled waste glasses and also discusses the manufacturing of GM for water filters and fillers for polymers.